New Surgical Model for Bone–Muscle Injury Reveals Age and Gender-Related Healing Patterns in the 5 Lipoxygenase (5LO) Knockout Mouse - Biguetti, Claudia Cristina; Couto, Maira Cristina Rondina; Silva, Ana Claudia Rodrigues; Shindo, João Vitor Tadashi Cosin; Rosa, Vinicius Mateus; Shinohara, André Luis; Andreo, Jesus Carlos; Duarte, Marco Antonio Hungaro; Wang, Zhiying; Brotto, Marco; Matsumoto, Mariza Akemi (Frontiers in Endocrinology, 2020)
Signaling lipid mediators released from 5 lipoxygenase (5LO) pathways influence both bone and muscle cells, interfering in their proliferation and differentiation capacities. A major limitation to study inflammatory signaling pathways in bone and muscle healing is the inadequacy of available animal models. We developed a surgical injury model in the vastus lateralis (VL) muscle and femur in 129/SvEv littermates mice to study simultaneous musculoskeletal (MSK) healing in male and female, young (3 months) and aged (18 months) WT mice compared to mice lacking 5LO (5LOKO). MSK defects were surgically created using a 1mm punch device in the VA muscle followed by a 0.5 mm round defect in the femur. After 7 and 14 days post-surgery, the specimens were removed for microtomography (microCT), histopathology, and immunohistochemistry analyses. In addition, non-injured control skeletal muscles, along with femur and L5 vertebrae were analyzed. Bones were microCT phenotyped, revealing that aged female WT mice presented reduced BV/TV and trabecular parameters compared to aged males and aged female 5LOKO mice. Skeletal muscles underwent a customized targeted lipidomics investigation for profiling and quantification of lipid signaling mediators (LMs) evidencing age and gender related-differences in aged female 5LOKO mice compared to matched WT. Histological analysis revealed a suitable bone healing process with osteoid deposition at day 7 post-surgery, followed by woven bone at day 14 post-surgery, observed in all young mice. Aged WT females displayed increased inflammatory response at day 7 post-surgery, delayed bone matrix maturation, and increased TRAP immunolabeling at day 14 post-surgery compared to 5LOKO females. Skeletal muscles of aged animals showed higher levels of inflammation in comparison to young controls at day 14 post-surgery; however, the inflammatory process was attenuated in aged 5LOKO mice compared to aged WT. In conclusion, this new model shows that MSK healing is influenced by age, gender, and the 5LO pathway, which might serve as a potential target to investigate therapeutic interventions and age-related MSK diseases. Our new model is suitable for bone-muscle crosstalk studies.